Antithrombotic Therapy in Patients with Paroxysmal Atrial Fibrillation after Catheter Treatment - O. R. Eshmatov; M. S. Khlynin; R. E. Batalov; E. A. Archakov; I. V. Kisteneva (Рациональная фармакотерапия в кардиологии)
Aim. To study the efficacy and safety of antithrombotic therapy in patients with paroxysmal atrial fibrillation (AF) after catheter treatment during 36 months of follow-up.Material and methods. The retrospective observational study included 592 patients (283 men) who underwent catheter treatment of AF, aged 26 to 86 years (median age was 61.0 [55; 67]) with paroxysmal AF, treated in cardiac arrhythmias department of the Institute of Cardiology of Tomsk National Research Medical Center from 01.01.2017 to 31.12.2019. All patients were retrospectively divided into 2 groups: the first group consisted of patients with effective AF ablation, the second - with ineffective AF ablation. During follow-up after 12, 24 and 36 months, patients' complaints, documented arrhythmia recurrences, adherence to the prescribed treatment, and adverse clinical events were taken into account.Results. In patients with paroxysmal AF, the effectiveness of catheter treatment was 73.1% after 12 months of follow-up, 69.3% – after 24 months, 71.6% – after 36 months. The analysis of our data showed that during the follow-up period of 36 months, the incidence of ischemic stroke against the background of anticoagulant therapy and effective catheter treatment of paroxysmal AF was significantly lower than in patients with unsuccessful ablation (0.3% (n=1) and 3.7% (n=4), respectively), even despite the fact that not all patients from the first group received prescribed medication.Conclusion. The use of anticoagulant therapy in patients with paroxysmal AF after interventional treatment is safe, since the invasive strategy in combination with anticoagulant therapy does not increase the risk of major and minor bleeding, and in the case of effective intervention allows statistically significantly reduce the risk of ischemic stroke and almost completely eliminate the likelihood of other thromboemolic complications.